THE RELATIONSHIP OF HAND WASHING BEHAVIOR TOWARDS DIARRHEA CASES IN SCHOOL-AGE CHILDREN - Ade Nuraeni; Rosiah, Rosiah; Megga Putri Kemala Supendi; Adhan Efendi (Universitas Airlangga, 2022)
Introduction: Hand washing is one of the current clean and healthy living behaviours that is a world concern. The problem of bad-hand washing behaviour not only occurs in developing countries but also in developed countries where most people still forget the importance of washing hands. The prevalence of diarrhoea among children aged 5-14 years reaches 182.338 (6.2%). The objective of this study was to determine the relationship between hand-washing behaviour and cases of diarrhoea in school-age children at Angkasa 2 Elementary School. Methods: This research method is quantitative, with a descriptive correlation research design, and uses a cross-sectional approach. The sample in this study was 63 respondents taken by purposive sampling. Data collection used questionnaires and observation sheets, analyzing data using a Chi-square test. Results: 73.01% of respondents had good hand-washing behaviour, while 26.98% had less hand-washing behaviour. Then, the respondents with good diarrhoea cases were 69.84%, and those with fewer diarrhoea cases were 30.15%. The statistical test showed a relationship between the variables of hand-washing behaviour with cases of diarrhoea (p =<0.001). Conclusions: There is a relationship between hand-washing behaviour and cases of diarrhoea in school-age children at Angkasa 2 elementary school. Hand washing is the most important basic technique in preventing and controlling the transmission of diarrheal diseases. It is necessary to have good facilities and knowledge about hand-washing, and the delivery of messages must be done recur so that understanding can align with these behavioural practices.